A compassionate spy [videorecording (DVD)] - James, Steve, 1955-; Hall, Theodore A. (Theodore Alvin), 1925-; Hall, Joan (Wife of Ted Hall) (Magnolia Home Entertainment, 2023)
Presents the story of Manhattan Project scientist Ted Hall, who shared classified nuclear secrets with Russia in an effort to save the world from nuclear annihilation.